T Cell Affinity Maturation by Selective Expansion during Infection - Busch, Dirk H. (The Rockefeller University Press, 1999)
T lymphocyte recognition of infected cells is mediated by T cell receptors (TCRs) interacting with their ligands, self–major histocompatibility complex (MHC) molecules complexed with pathogen-derived peptides. Serial TCR interactions with potentially small numbers of MHC/ peptide complexes on infected cells transmit signals that result in T lymphocyte expansion and activation of effector functions. The impact of TCR affinity for MHC/peptide complexes on the rate or extent of in vivo T cell expansion is not known. Here we show that in vivo expansion of complex T cell populations after bacterial infection is accompanied by an increase in their overall affinity for antigen. T cell populations that have undergone additional rounds of in vivo expansion express a narrower range of TCRs, have increased sensitivity for antigen in cytotoxic T lymphocyte assays, and bind MHC/peptide complexes with greater affinity. The selective expansion of higher affinity T cells provides an in vivo mechanism for optimizing the early detection of infected cells.